Impact of Cooking Temperature on In Vitro Starch Digestibility of Rice Varieties with Different Amylose Contents - Guillén Sofía; Oria Rosa; Salvador María Luisa (Polish Journal of Food and Nutrition Sciences)
The aim of this study was to evaluate the effect of cooking temperature on the in vitro starch digestibility of four varieties of rice: Basmati, Calrose, Arborio and Bomba. Total starch, resistant starch and amylose contents were determined in raw and cooked samples. The in vitro kinetics of starch hydrolysis were also determined, and the hydrolysis and glycemic indexes were estimated. Both the initial amylose content and the cooking temperature had a significant influence on the resistant starch content. Rice cooked at 95ºC retained a higher resistant starch content than rice cooked at 100ºC. The in vitro study of starch hydrolysis showed that hydrolysis tended to be slower and less complete for rice with a higher amylose content and for rice cooked at a lower temperature. Cooking rice at 95ºC instead of 100ºC reduced the estimated glycemic index by approximately 10% for the varieties tested.